The impact of the strategic foresight capabilities in green creativity An exploratory study for the State Company for Food Products - Habib, Asmaa; Abdulraheem, Sanaa (Journal of Economics and Administrative Sciences, 2021)
The current research variables have received increasing attention in the recent period because they are one of the important issues affecting the future of organizations, as a result of the speed of environmental variables that have greatly affected organizations and for the purpose of explaining the relationships and links between research variables, as this research presents a test "the type and direction of the relationship between strategic foresight capabilities As an independent variable and green creativity "as a respondent variable. A set of questions has arisen about the basic research problem, including what is the nature and level of interest in the research variables (strategic foresight capabilities and urban creativity) in the research sample company, a set of goals have been formulated, including testing and determining the relationship of strategic foresight capabilities to creativity The presence in the researched company, and for this purpose, a number of hypotheses were formulated, the most important of which was finding a correlation and impact relationship (strategic foresight capabilities and dimensions with urban creativity) and to achieve hypothesis tests field research was used and applied to a sample of department heads and people in the General Company for Food Products, The number of individuals in the sample was (116) individuals, and data was collected through questionnaire and the use of clothes She has seen the field and personal interviews with a number of department heads. A number of statistical methods were used to process the data, including the mean, the percentage, the standard deviation, for the purpose of describing the sample, and the simple linear correlation coefficient (Pearson) to test the validity of the hypotheses correlation and simple and multiple linear regression to test the validity of the effect, and the data was analyzed via A set of statistical programs are (SPSS, Amos, PPR 2.16.3) and the use of linear programming to determine the production size of the research sample company. As for the most prominent conclusions, it was represented: that all of the relationships of strategic exploration with, and civil creativity were good and significant. The research concluded with a set of recommendations, one of the most important of which was: The company must devote its efforts in the areas of strategic foresight capabilities and employ them to achieve and achieve green creativity through special programs prepared for this purpose